Frequency of Paroxysmal Nocturnal Hemoglobinuria Clone in Turkish Myelodysplastic Syndrome Group - (:unkn) unknown (GALENOS YAYINCILIK, 2018)
Aim: Retrospective, cross-sectional, observational study to examine the frequency and features of paroxysmal nocturnal hemoglobinuria (PNH) clones in patients with myelodysplastic syndrome (MDS). Methods: Data were analyzed from the medical files of 41 MDS patients diagnosed and followed up in the hematology department at a referral center between 2006 and 2017. Descriptive data, cytogenetic and hematologic characteristics, prognostic features and PNH clone sizes were assessed. PNH clone sizes were evaluated using the fluorescently labeled inactive toxin aerolysin method. Results: The study population comprised 22 (53.7%) female and 19 (46.3%) male patients with confirmed MDS; the mean age of the patients was 68.20 +/- 9.84 years (range, 45-85). PNH clones were detected in eight (19.5%) patients. The number of patients with a PNH clone size of > 10%, > 1%, > 0.1% and > 0.01% was one, one, one and eigth, respectively (p< 0.001 for all subgroups). Conclusion: These data indicate that PNH clones exist in approximately one-fifth of MDS patients. Further studies on a more extensive cohort are required to better understand the pathophysiological and clinical relationships between MDS and PNH.
Keywords: Paroxysmal nocturnal hemoglobinuria; myelodysplastic syndrome; FLAER; BONE-MARROW FAILURE; APLASTIC-ANEMIA; CELLS; MANAGEMENT; DIAGNOSIS; LEUKEMIA; PNH